2017
DOI: 10.1038/s41598-017-16759-7
|View full text |Cite
|
Sign up to set email alerts
|

Persistent inhibition of pore-based cell migration by sub-toxic doses of miuraenamide, an actin filament stabilizer

Abstract: Opposed to tubulin-binding agents, actin-binding small molecules have not yet become part of clinical tumor treatment, most likely due to the fear of general cytotoxicity. Addressing this problem, we investigated the long-term efficacy of sub-toxic doses of miuraenamide, an actin filament stabilizing natural compound, on tumor cell (SKOV3) migration. No cytotoxic effects or persistent morphological changes occurred at a concentration of miuraenamide of 20 nM. After 72 h treatment with this concentration, nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…These results indicate that MiuA has an overall effect on both cell motility and directionality of the movement, both in a simple 2D and in more physiological 3D environments. The reduced velocity in the 3D system could be explained by the cells having a reduced ability to squeeze through a small meshwork, as we have previously described 11 .…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…These results indicate that MiuA has an overall effect on both cell motility and directionality of the movement, both in a simple 2D and in more physiological 3D environments. The reduced velocity in the 3D system could be explained by the cells having a reduced ability to squeeze through a small meshwork, as we have previously described 11 .…”
Section: Resultsmentioning
confidence: 64%
“…The myxobacterial compound miuraenamide A (MiuA) 25 is also structurally related to these compounds, and has turned out to have a functional profile similar to phalloidin or jasplakinolide (enhanced polymerization and stabilization, cell morphology and cytotoxicity) 9,10 . We have previously used MiuA as a bona fide actin polymerizing compound in cellular studies, and have shown effects on cell migration and transcriptional activity that can be ascribed to its actin stabilizing nature 11,26 . In the present study we established dose response curves for MiuA on proliferation in primary endothelial cells (HUVECs), which are similar to those in tumor cell lines 9,11 , and lie in the same range as those for jasplakinolide 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogously, the myxobacterial compound miuraenamide A binds to and stabilizes F-actin by competing with ADF/cofilin for its binding site [ 421 ]. Interestingly, low-dose treatment of SKOV3 and HUVECs cells with miuraenamide A showed no effects on cell viability and proliferation, while actin structure was initially subtly changed, but recovered subsequently [ 422 ].…”
Section: Therapeutic Opportunities For Cytoskeleton-related Forms Of Id and Related Conditionsmentioning
confidence: 99%
“…18,19 The same effects were also observed for the geodiamolides, 17 chondramides 20,21 and the miuraenamides. [22][23][24] While the other natural products contain six to seven stereogenic centres, the miuraenamides A-C contain only three asymmetric Catoms (and one stereoisomeric double bond). Therefore, the miuraenamides might be ideal candidates for the development of potential anti-tumor drugs.…”
Section: Introductionmentioning
confidence: 99%